School harassment and assertiveness at a national secondary school in Chimbote, Peru - Rodríguez Jara, Diana Deissy (2017)
In this study it considered as aim to determine the relation that exists between the School Harassment and Asertividad in students of Secondary Education. The sample of study was constituted by 273 students of 1° to 5° of Secondary Education of both sexes for the above mentioned study Autotes Cisneros's instruments were in use for School Harassment of Oñate and Piñuel (2007) and ADCA-1 for Asertividad de García and Magáz (1994). Finding correlations in Autoasertividad's scale and scales of school harassment between,-311 to-, 542, (p <.01). Also I demonstrate correlations in Heteroasertividad's scale and the scales and school harassment between-, 113 to-, 400 (p <.01). Likewise, one thought that Autoasertividad's scale has a predominance of average level 44.0 % and the high level with 29.3 % and with what concerns the Heteroasertividad also one exists I predominate of the average level with 42.1 % and the high level over 29.7 %, on the other hand in you her climb of school harassment in the level of utilization " always or almost always " it ranges between 24.2 % in the scales of Social Exclusion -blockade and I steal 37.7 % in the scale of harassment